Access to and utilization of prenatal care services in the Unified Health System of the city of Rio de Janeiro, Brazil - Rosa Maria Soares Madeira Domingues; Maria do Carmo Leal; Zulmira Maria de Araújo Hartz; Marcos Augusto Bastos Dias; Marcelo Vianna Vettore (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
Prenatal care consists of practices considered to be effective for the reduction of adverse perinatal outcomes. However, studies have demonstrated inequities in pregnant women's access to prenatal care, with worse outcomes among those with lower socioeconomic status. The objective of this study is to evaluate access to and utilization of prenatal services in the Sistema Único de Saúde (SUS - Unified Health System) in the city of Rio de Janeiro and to verify its association with the characteristics of pregnant women and health services. A cross-sectional study was conducted in 2007-2008, using interviews and the analysis of prenatal care cards of 2.353 pregnant women attending low risk prenatal care services of the SUS. A descriptive analysis of the reasons mentioned by women for the late start of prenatal care and hierarchical logistic regression for the identification of the factors associated with prenatal care use were performed. The absence of a diagnosis of pregnancy and poor access to services were the reasons most often reported for the late start of prenatal care. Earlier access was found among white pregnant women, who had a higher level of education, were primiparous and lived with a partner. The late start of prenatal care was the factor most associated with the inadequate number of consultations, also observed in pregnant adolescents. Black women had a lower level of adequacy of tests performed as well as a lower overall adequacy of prenatal care, considering the Programa de Humanização do Pré-Natal e Nascimento (PHPN - Prenatal and Delivery Humanization Program) recommendations. Strategies for the identification of pregnant women at a higher reproductive risk, reduction in organizational barriers to services and increase in access to family planning and early diagnosis of pregnancy should be prioritized.